A bioinspired and hierarchically structured shape-memory material - Cera, Luca; Gonzalez, Grant M.; Liu, Qihan; Choi, Suji; Chantre, Christophe O.; Lee, Juncheol; Gabardi, Rudy; Choi, Myung Chul; Shin, Kwanwoo; Parker, Kevin Kit (Nature materials, 2021)
Shape-memory polymeric materials lack long-range molecular order that enables more controlled and efficient actuation mechanisms. Here, we develop a hierarchical structured keratin-based system that has long-range molecular order and shape-memory properties in response to hydration. We explore the metastable reconfiguration of the keratin secondary structure, the transition from α-helix to β-sheet, as an actuation mechanism to design a high-strength shape-memory material that is biocompatible and processable through fibre spinning and three-dimensional (3D) printing. We extract keratin protofibrils from animal hair and subject them to shear stress to induce their self-organization into a nematic phase, which recapitulates the native hierarchical organization of the protein. This self-assembly process can be tuned to create materials with desired anisotropic structuring and responsiveness. Our combination of bottom-up assembly and top-down manufacturing allows for the scalable fabrication of strong and hierarchically structured shape-memory fibres and 3D-printed scaffolds with potential applications in bioengineering and smart textiles. Shear-aligned keratin protofibres are used to fabricate shape-memory fibres and three-dimensional scaffolds that respond to water.